Understanding the interaction between wheat starch and Mesona chinensis polysaccharide. (October 2017) - Yuris, Anynda; Goh, Kelvin Kim Tha; Hardacre, Allan Keith; Matia-Merino, Lara
Abstract: In order to elucidate the mechanism of interaction between Mesona chinensis polysaccharide (MCP) and wheat starch, the granular swelling, amylose leaching, and gelatinisation properties of 20 mg wheat starch/g suspension were studied in the presence of increasing concentrations of MCP. At room temperature, the presence of MCP (0.2–15.8 mg/g suspension) induced shear-reversible starch aggregation. Heating of starch-MCP suspension resulted in an earlier onset of viscosity that was characterised by a peak "M". This was also accompanied by delayed granular swelling and a 40% reduction in amylose leaching when 11.3 mg MCP/g suspension was present. An interaction was thought to occur when amylose leaches out of wheat starch granules forming an MCP-amylose barrier, increasing the apparent size of the granules. The final G ′ of starch gel (∼1 Pa) increased during cooling in the presence of increasing concentrations of MCP up to 20 Pa with 11.3 mg MCP/g suspension, indicative of a 3D network comprising of amylose, MCP and starch granules. The final gel properties were dependent on the concentration of MCP present whereby an extensive MCP-amylose network was required to stabilise the starch granule aggregates despite a reduction in the amount of amylose leached. Highlights: Mesona chinensis polysaccharide induced starch aggregation at room temperature. Mesona chinensis polysaccharide delayed starch granular swelling and gelatinisation. Mesona chinensis polysaccharide reduced wheat starch amylose leaching. An interaction between Mesona chinensis polysaccharide and amylose was evident. Starch gel strength was influenced by Mesona chinensis polysaccharide concentration.